Potential molecular mechanisms for fruiting body formation of Cordyceps illustrated in the case of Cordyceps sinensis - Kun Feng; Lan-ying Wang; Dong-jiang Liao; Xin-peng Lu; De-jun Hu; Xiao Liang; Jing Zhao; Zi-yao Mo; Shao-ping Li (Mycology, 2017)
The fruiting body formation mechanisms of Cordyceps sinensis are still unclear. To explore the mechanisms, proteins potentially related to the fruiting body formation, proteins from fruiting bodies, and mycelia of Cordyceps species were assessed by using two-dimensional fluorescence difference gel electrophoresis, and the differential expression proteins were identified by matrix-assisted laser desorption/ionisation tandem time of flight mass spectrometry. The results showed that 198 differential expression proteins (252 protein spots) were identified during the fruiting body formation of Cordyceps species, and 24 of them involved in fruiting body development in both C. sinensis and other microorganisms. Especially, enolase and malate dehydrogenase were first found to play an important role in fruiting body development in macro-fungus. The results implied that cAMP signal pathway involved in fruiting body development of C. sinensis, meanwhile glycometabolism, protein metabolism, energy metabolism, and cell reconstruction were more active during fruiting body development. It has become evident that fruiting body formation of C. sinensis is a highly complex differentiation process and requires precise integration of a number of fundamental biological processes. Although the fruiting body formation mechanisms for all these activities remain to be further elucidated, the possible mechanism provides insights into the culture of C. sinensis.